YES VIRGINIA, THERE IS RIGHT AND WRONG (Author: Kathleen M. Gow) - Cassidy, Brian (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1981)
Kathleen M. Gow. YES VIRGINIA, THERE IS RIGHT AND WRONG. Toronto: John Wiley &: Sons Canada Ltd., 1980. 248 pp. $8.95.